The Effectiveness of PowToon Audiovisual Media on Mathematics Learning Three-Dimensional Geometry Object Elementary School - Elly Anjarsari; Dwi Juniati; Siti Khabibah (Vygotsky: Jurnal Pendidikan Matematika dan Matematika, 2023)
This research is a descriptive study with the aim of knowing the effectiveness of the PowToon audiovisual media in mathematics learning for elementary school students, with is viewed from three indicators, namely (1) the activity of students during PowToon audiovisual media, (2) student learning outcomes, and (3) students positive responses after participating in learning using PowToon audiovisual media. The results showed that mathematics learning using PowToon audiovisual media was effective. The learning outcomes of students after participating in learning using the PowToon audiovisual media were complete, with a classical percentage of 85,19%. Students positive responses to mathematics learning using PowToon audiovisual media meet the effectiveness criteria with 88,5% of student responses reaching the positive category.